Stem cell function during plant vascular development - Miyashima, Shunsuke (European Molecular Biology Organization, 2013)
The plant vascular system, composed of xylem and phloem, evolved to connect plant organs and transport various molecules between them. During the post-embryonic growth, these conductive tissues constitutively form from cells that are derived from a lateral meristem, commonly called procambium and cambium. Procambium/cambium contains pluripotent stem cells and provides a microenvironment that maintains the stem cell population. Because vascular plants continue to form new tissues and organs throughout their life cycle, the formation and maintenance of stem cells are crucial for plant growth and development. In this decade, there has been considerable progress in understanding the molecular control of the organization and maintenance of stem cells in vascular plants. Noticeable advance has been made in elucidating the role of transcription factors and major plant hormones in stem cell maintenance and vascular tissue differentiation. These studies suggest the shared regulatory mechanisms among various types of plant stem cell pools. In this review, we focus on two aspects of stem cell function in the vascular cambium, cell proliferation and cell differentiation.